(3x – 4)^{3} + (6x – 3)^{3} + (3x – 3)^{3} = 9 (4 – 3x) (2x – 1) (3 – 3x), then find the value of x.

- 1
- 2/3
- 3/4
- 5/6

Option 4 : 5/6

**Given : **

(3x – 4)^{3} + (6x – 3)^{3} + (3x – 3)^{3} = 9 (4 – 3x) (2x – 1) (3 – 3x)

**Formula used :**

,a^{3} + b^{3} + c^{3} = 3abc when a + b + c = 0

**Calculations :**

(3x – 4)^{3} + (6x – 3)^{3} + (3x – 3)^{3} = 9 (4 – 3x) (2x – 1) (3 – 3x)

⇒ 3 (3x – 4) [3 × (2x – 1)](3x – 3)

⇒ 3 (3x – 4)(6x – 3)(3x – 3)

This equation is comparable with above given formula

So,

3x – 4 + 6x – 3 + 3x – 3 = 0

12x – 10 = 0

12x = 10

,x = 5/6

**∴ Option 4 will be the correct choice.**

India’s **#1 Learning** Platform

Start Complete Exam Preparation

Daily Live MasterClasses

Practice Question Bank

Mock Tests & Quizzes

Trusted by 2,18,08,573+ Students

Testbook Edu Solutions Pvt. Ltd.

1st & 2nd Floor, Zion Building,

Plot No. 273, Sector 10, Kharghar,

Navi Mumbai - 410210

[email protected]
Plot No. 273, Sector 10, Kharghar,

Navi Mumbai - 410210

Toll Free:1800 833 0800

Office Hours: 10 AM to 7 PM (all 7 days)